FORMER COMMUNIST ILLEGALS-INVESTIGATORS OF THE SPECIAL POLICE IN OCCUPIED BELGRADE (1941−1944) (Heritage, 2021)
The paper analyzes the activities of Special Police investigators, former members of the communist movement in Belgrade. Recruiting detainees for secret cooperation with the Special Police was a practice that lasted throughout World War II. These people became confidants, and they returned to the organization and caused serious damage to the work of the Communist Party. Božidar Bećarević, the head of the IV anti-communist department, tried to hire certain communist officials not only as confidants but also as responsible officials who enjoyed the status of investigators or agents. In that sense, the most prominent were Branko Mišković Bliher, Tenko Dalvović and Dušan Jovanović Žuća.During the war, agents and investigators of the Special Police were hated by citizens, especially communist illegals, for their arrogant behavior and very cruel treatment of detainees. That hatred was especially strong towards those who were once members of the communist movement themselves. They were especially zealous in arresting, harassing and killing their former party comrades, wanting to prove themselves before the collaborationist and occupying authorities. Some of them changed sides several times, trying to assess the course of the war and on that basis moving from one camp to another. Some, like Dušan Jovanović Žuća, tried again to renew their cooperation with the communist movement, and in the end they ended up being shot as communists, essentially hated on both sides as traitors. It is not possible to determine exactly the number of confidants who cooperated with the Special Police because this information was kept strictly secret. There is little more information about those who openly agreed to cooperate and became investigators, and almost as a rule most of them lost their lives by being killed by communists or patriots during the war.
Keywords: World War II, Special Police, Belgrade, Dušan Jovanović Žuća, Communist Party of Yugoslavia, Anti-Communist Department, investigators